2020
DOI: 10.1021/acs.langmuir.0c02754
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Role of Oxide–Oxide/Carbon Interfaces of CuOx–CeO2/C in Boosting Electrocatalytic Performance

Abstract: Herein, we report the synthesis and bifunctional oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) activities of a CuO x −CeO 2 /C electrocatalyst (EC) with rich oxide−oxide and oxide−carbon interfaces. It not only demonstrates a smaller Tafel slope (65 mV dec −1 ) and higher limiting current density (−5.03 mA cm −2 ) but also exhibits an onset potential (−0.10 V vs Ag/AgCl) comparable to that of benchmark Pt/C. Besides undergoing the favorable direct four-electron ORR pathway, it unveils a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 70 publications
2
31
0
Order By: Relevance
“…78 Through the similar process, Bharali and coworkers synthesized a nanostructured CuO x -CeO 2 /C electrocatalyst with abundant surface oxygen vacancies and distinguished oxide-oxide/carbon interfaces. 79 Worthy of note, Ni and coworkers developed a novel CeO 2 /LaFeO 3 hybrid via a facile chemical bath method.…”
Section: First-row Tmosmentioning
confidence: 99%
“…78 Through the similar process, Bharali and coworkers synthesized a nanostructured CuO x -CeO 2 /C electrocatalyst with abundant surface oxygen vacancies and distinguished oxide-oxide/carbon interfaces. 79 Worthy of note, Ni and coworkers developed a novel CeO 2 /LaFeO 3 hybrid via a facile chemical bath method.…”
Section: First-row Tmosmentioning
confidence: 99%
“…Our previous work also revealed that the CuO x −CeO 2 /C EC exhibited high performance toward the ORR and OER compared to their single MOs. 24 Oxygen electrocatalysis, nowadays, is highly prioritized due to its significant role in the productivity of alternative energy devices, such as metal−air batteries, 20 fuel cells (FCs), 25 and electrolyzers, 26 which delivers power at decent rates. The two dominant electrode reactions occurring in such energy devices are the ORR and OER.…”
Section: Introductionmentioning
confidence: 99%
“…The electrocatalytic ORR activity is studied via cyclic voltammetry (CV) and linear sweep voltammetry (LSV) methods. [14,15] LSV is generally recorded by rotating disk electrode (RDE) and rotating ring disk electrode (RRDE). These rotation dependent techniques offer good control of the reaction hydrodynamics by creating a laminar flux of analyte toward and outward the rotating electrode surfaces.…”
Section: Fundamentals Of Orrmentioning
confidence: 99%
“…The electrocatalytic ORR activity is studied via cyclic voltammetry (CV) and linear sweep voltammetry (LSV) methods [14,15] . LSV is generally recorded by rotating disk electrode (RDE) and rotating ring disk electrode (RRDE).…”
Section: Introductionmentioning
confidence: 99%